A Hybrid Approach to Right-sided Aortic Arch Aneurysm Using Bilateral Carotid to Subclavian Bypass with a Customized Fenestrated Thoracic Endovascular Aortic Repair Device - Victoria A. Burrows; Siuchan Sookhoo (The Arab Journal of Interventional Radiology, 2018)
We present a hybrid approach to the management of an aortic aneurysm in a right-sided aortic arch with aberrant left subclavian artery and associated Kommerell's diverticulum. The aneurysm extended from the origin of the left common carotid artery to the mid-descending thoracic aorta. A bilateral carotid to subclavian artery bypass was performed followed by endovascular placement of a customized fenestrated thoracic endovascular aortic repair device (TEVAR, Cook Medical, Australia). Endovascular stents (Viabahn, Gore Medical, Arizona) were placed in the carotid arteries bilaterally and Amplatzer II plugs (AGA Medical Corporation) were used to occlude the subclavian arteries. Follow-up imaging at 1 month revealed no evidence of endoleak.